New insights toward personalized therapies for vulvovaginal candidiasis and vaginal co-infections - De Seta, Francesco; Warris, Adilia; Roselletti, Elena (Frontiers in Microbiology, 2025)
Lower genital tract infections, particularly vulvovaginal candidiasis (VVC) and bacterial vaginosis (BV), are among the most prevalent infections in women worldwide, especially those of reproductive age. These conditions not only cause significant clinical symptoms but also severely impact women’s quality of life and mental health. Despite extensive research on the pathogens involved, substantial gaps remain in understanding the vaginal immune response and the complexity of the vaginal ecosystem, which is largely shaped by a Lactobacillus-dominated microbiota and the high concentration of lactic acid, contributing to the vagina’s unique acidic pH. This review explores the underlying pathophysiology of VVC, BV, and fungal-bacteria co-infections, as well as conventional and emerging treatments, including zinc, Lactobacillus spp., and lactic acid. The challenges of antifungal drug resistance are also discussed, in parallel with immune cell dysfunction and its potential link to the vaginal microbiota and ecosystem. Personalized treatments and approaches tailored to the individual vaginal environment are essential for maintaining eubiosis and preventing recurrent infections. Future research should prioritize modulating host and environmental factors rather than targeting pathogens alone, to develop targeted therapies that prevent reinfection, minimize side effects, reduce development of drug-resistance, and ultimately improve women’s health outcomes.